PENYELESAIAN WANPRESTASI TERHADAP PERJANJIAN SEWA MENYEWA MENURUT HUKUM ISLAM - Al Furqan; Siti Nabila; Muammar Kadafi; Fuja Afiska (LPPM IAI Almuslim Aceh, 2026)
This study aims to analyze the resolution of breach of contract in lease agreements under Islamic law. A breach (wanprestasi) in an ijarah (lease) contract occurs when one party fails to fulfill agreed obligations, such as late payment, misuse of the leased object, or violation of contractual terms. In Islamic law, the resolution of such breaches emphasizes the principles of justice (‘adl), public interest (maslahah), and good faith between the parties. Dispute resolution is primarily conducted through mutual deliberation (ṣulḥ) to reach an amicable settlement without harming either party. If such efforts fail, the dispute may be brought before judicial institutions, where decisions are made based on evidence and sharia principles. Sanctions for breach in Islamic law are not punitive in nature but aim to restore rights and obligations proportionally, including compensation (ta‘wīḍ) for actual losses incurred. Additionally, contract termination (fasakh) may be applied in cases of substantial violation. Therefore, the resolution of breach of contract in Islamic law highlights a balance between enforcement of rights, responsibilities, and moral values grounded in sharia principles.